Autism: an everyday reality (Journal of Parents and Teachers, 2014)
In this article, two parents tell the emotional story of their child who suffered from what is called Autistic Regression (losing skills that had already been acquired). They also explain how they found out exactly what happened to their child and how, with a lot of patience, motivation, love, and help, they were able to help their child.
Keywords: autism; children; family; relationship; parents; kids